(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
Given the importance of assessing the risk of recurrence and escalation of violence for the prevention and fight against gender-based violence, the present paper emphasises the need to introduce specific assessment procedures, targeted and calibrated to the vulnerability of victims. Furthermore, the essay reconstructs the framework of algorithmic systems currently used in this field, the challenges they pose on a technical as well as ethical and legal level, and their potential developments. Finally, using the symbiotic paradigm, the paper provides suggestions for the acceptance of artificial intelligence in this sensitive area.